Operational cost optimization on solid waste collection using goal programming/ Diana Sirmayunie Mohd Nasir, Salwani Asman and Suzanawati Abu Hasan - Mohd Nasir, Diana Sirmayunie; Asman, Salwani; Abu Hasan, Suzanawati (Universiti Teknologi MARA, Perak, 2024)
Waste collection is the waste management, comprising storage, collection, transportation, and disposal, is the most expensive aspect of waste management, involving resources in strategy, execution, and oversight. Even in Perlis, the smallest state in Malaysia, waste management has become a concern due to population growth and increased industrial activities. This study aims to determine the optimal operational cost by utilizing the Goal Programming approach. Data from E-Idaman Kangar Sdn. Bhd, a private company managing solid waste in Perlis, was utilized. The goal is to achieve an optimization rate by formulating an objective function and utilizing Lingo software version 18.0. The study aims to achieve five objectives regarding operational cost which are minimizing labor cost, minimizing collection cost, minimizing vehicle cost, minimizing consumable cost and minimizing the financial statement of operation for each route. The research results indicate that E-Idaman Kangar's collection expenses are already at an optimal state. It showed that the cost of each vehicle included in the collection activity is optimized. The objective value shows that the total spending can still be reduced by RM3, which is a decrease of 0.01%. In conclusion, this can be seen that the organization accomplishes collection in an ideal manner. The outcomes of this study are poised to contribute towards achieving sustainable Solid Waste Collection (SWC) across the entirety of Perlis state, thereby upholding a clean and healthy environment for its residents. Additionally, through meticulous budgeting and strategic planning prior to each monthly collection, companies can effectively manage their finances and bolster profitability.